From fishing villages to international tourist destinations: where are the citizens? : The cases of Cabo Frio, Rio de Janeiro and Porto Seguro, Bahia - Brazil - Araujo, Cristina Pereira; Abreu, Luciano Muniz (Sociedade & Natureza, 2021)
The present article examines the relationship between tourism, production of space and the role of residents at two hotspot tourist destinations in Brazil: Cabo Frio, located in State of Rio de Janeiro and Porto Seguro, in State of Bahia. The development of the tourist industry in the localities under study occurred at different points in time. In the first, the urbanization process was associated with the acquisition of second homes in the 1950s, while the second, located in the Northeast region of the country, this process emerged in conjunction with the mass tourism industry only in the late 1980s. We hope this research will enhance understanding of the process of urbanization and the configuration of tourism space and the conflicts arising from this in developing countries, notably Latin America. Our methodology employed theories based on those developed by Chesnais (1996, 2005, 2016), Harvey (2005, 2008, 2011, 2014), Santos (2006) and others to explain the production of space in a way that goes beyond the use of historical data and socioeconomic analysis. The initial conclusion was that, despite the differences in the process (mass tourism vs. second homes, development in space and over time and geographical position), the two geographical locations selected presented the same findings: unequal production of space and the exclusion of local populations. The tourism activity investigated in these two case studies thus appears to replicate the current stage of development in Brazil, characterized by inequality and exclusion and reflected in the landscapes of the country’s tourist destinations.